Da'wah Patterns through Local Culture of Gesrek Art in Kombongan Village, Garut Regency - Deni Miharja; Ipan Rifani (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2021)
The purpose of this study was to determine the art of Gesrek as a medium of cultural da'wah and the pattern of da'wah in the local culture of Gesrek art. The research was conducted in Kombongan Village, Pakenjeng Village, Pamulihan District, Garut Regency. The choice of this place was based on the growth and development of the art of Gesrek as one of the local pearls of wisdom of the Garut people. The research was conducted with a qualitative approach through descriptive methods. Where the researcher collects data through observation and in-depth interviews in order to be able to compare the data in the field and the literature review according to the research topic, the results showed that Gesrek art could be used as an effective cultural propaganda medium because this art contains practices that are following Islamic teachings both at the pre-implementation stage and at the time of implementation. The da'wah pattern of dialogue is a form of interaction between Islam and local culture in the art of Gesrek. This is marked by the content of the prayer and the behavior of the art following Islamic teachings and sharia, such as readings sourced from Al-Quran verses and rituals prior to their implementation that follow Islamic teachings.